Effects of student's satisfaction and co-creation on the relationship between attitudinal factors and destination loyalty: Evidence from international students in Malaysian public universities - Ndaaba, Ndanusa, Mohammed Manzuma (School of Business Innovation & Technopreneurship, 2017)
This study conducted its investigation within the following scopes; this study was limited to public universities in Malaysia. In short, private institutions/universities are not involved for three main reasons; first, public universities are not fully marketized compared to private but yet students were charged tuition fee and other sundry bills. These universities were not only limited in number but are accessible. Secondly, affordability of fee and varieties of programs of study at these universities could trigger students' loyalty behavior. Thirdly, university selection is tied to universities rating and ranking globally, and Malaysian public universities are visible on the list than private; data for this study were limited to international students (undergraduate and postgraduate) holding student pass from selected public universities in Malaysia based on defined sample procedure; the research framework in this study is limited to the identified attitudinal factors: service quality, perceived value, satisfaction, perceived image, personal reasons and destination loyalty. The moderation effects of Co-Creation were also explored in the relationship as recommended by previous literatures.